Optimisasi Web Service REST API Menggunakan Load Balancer dan Cache dengan Algoritma Round Robin (Studi Kasus: Madani Infosphere) - Junaedy, Fadida Zanetti; Surapati, Untung (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
In today's digital era, the use of REST API Web Services is increasing, becoming a major foundation in web application development due to its simplicity and scalability. However, increased demand and data complexity often lead to a decrease in Web Service performance, especially in terms of response time and service availability. This research focuses on the performance optimisation of Madani Infosphere Web Service, an information platform developed by the non-profit organisation MADANI Berkelanjutan. This platform previously used a single server architecture that was prone to performance issues. To overcome this, this research applies load balancer technology with a round robin algorithm to distribute the workload evenly across multiple servers and uses a cache to store frequently accessed data. The results show that the use of load balancer with round robin algorithm is effective in overcoming potential server overload, making Web Service performance more stable and responsive. In addition, the cache implementation successfully reduces server workload and speeds up response time. Thus, this optimisation can improve the efficiency and availability of Madani Infosphere Web Services.